O IDEB como política de regulação do Estado e legitimação da qualidade: em busca de significados - Chirinéa, Andréia Melanda; Brandão, Carlos Da Fonseca [UNESP] (Fundação CESGRANRIO, 2015)
Abstract This paper discusses the quality of basic education legitimized by the external evaluation and publicized by the Basic Education Development Index (IDEB) - an index that combines the performance of students in the assessment and the school flow, culminating with the establishment of an objective parameter (grade) that aims to reflect the Brazilian educational quality. The arguments are based on the premise that these two elements are incipient to determine the quality of education in the country without taking into account other factors that affect quality, namely: socio-economic and cultural level of the students, teacher training, enhancement of teaching, tangible and intangible working conditions, school management, school infrastructure, supplies, etc. The reflection leading to the debate on the lack of evidence to establish the quality of education travels the ways of the external evaluation in Brazil, the technical rationality of the school management referenced primarily by the IDEB and its governance to achieve the goals determined by this index. The purpose of this essay is to contribute to the current debate on the IDEB as a proposer and mobilizer of policies for the Brazilian public schools.

Resumen Este trabajo analiza la calidad de la educación básica legitimada por la evaluación externa y publicada por el Índice de Desarrollo de la Educación Básica (IDEB). Índice que combina el rendimiento de los estudiantes en la evaluación y el flujo de la escuela, que culminó con el establecimiento de un parámetro objetivo (nota) cuyo objetivo es reflejar la calidad de la educación brasileña. Los argumentos basados en la premisa de que estos dos elementos son incipientes para determinar la calidad de la educación en el país, sin tener en cuenta otros factores que afectan a la calidad, a saber: el nivel socioeconómico y cultural de los estudiantes, la formación del profesorado, la mejora de enseñanza y de las condiciones tangibles e intangibles de trabajo, la gestión escolar, la infraestructura escolar, los insumos, etc. La reflexión que permita el debate sobre la falta de pruebas para establecer la calidad de la educación, recorre los caminos de la evaluación externa en Brasil, de la racionalidad técnica en gestión escolar referida principalmente por IDEB y su gobernabilidad para alcanzar los objetivos determinados por el índice. Con este ensayo se busca contribuir al debate actual sobre el IDEB como elemento impulsor y movilizador de políticas en las escuelas públicas brasileñas.

Resumo Este trabalho procura discutir a qualidade da educação básica, legitimada pela avaliação externa e divulgada pelo Índice de Desenvolvimento da Educação Básica (IDEB). Esse índice combina o desempenho dos alunos na avaliação e o fluxo escolar, culminando no estabelecimento de um parâmetro objetivo (nota), que pretende refletir a qualidade educacional brasileira. As argumentações partem da premissa de que estes dois elementos são incipientes para determinar a qualidade educacional do país, na medida em que não se levam em conta os demais fatores que incidem sobre a qualidade, quais sejam: nível socioeconômico e cultural dos alunos; formação docente; valorização do magistério; condições materiais e imateriais de trabalho; gestão escolar; infraestrutura da escola, e insumos, entre outros. A reflexão que conduz ao debate sobre a insuficiência de elementos para estabelecer a qualidade da educação percorre os caminhos da avaliação externa no Brasil, da racionalidade técnica da gestão escolar referenciada primordialmente pelo IDEB e sua governabilidade, para atingir as metas determinadas pelo índice. Procura-se, com este ensaio, contribuir para o debate atual sobre o IDEB enquanto propositor e mobilizador de políticas nas escolas públicas brasileiras.
The IDEB as state regulatory policy and legitimation of quality: in search of meaning
IDEB como política de regulación estatal y legitimación de la calidad: en busca de sentido
Keywords: Management; Public school; Educational quality; External evaluation; Gestão; Escola pública; Qualidade educacional; Avaliação externa